A Short Review of the Recent Literature on Uncertainty. (March 2017) - Castelnuovo, Efrem; Lim, Guay; Pellegrino, Giovanni
Abstract: This article summarises the academic contributions presented and discussed during the 2016 edition of the Melbourne Institute Macroeconomic Policy Meetings, which focused on the role played by uncertainty for a number of countries' business cycle. Considerations on the interaction between uncertainty and financial frictions, the global dimension of uncertainty, uncertainty shocks in times of unconventional monetary policy and the imperfect knowledge that agents have over policy targets are among the discussions entertained in this article. The main insights coming from those papers are connected with the extant literature and directions for future research are offered.